Construction and reconstruction of brain circuits: normal and pathological axon guidance. Issue 1 (21st November 2019) - Roig-Puiggros, Sergi; Vigouroux, Robin J.; Beckman, Danielle; Bocai, Nadia I.; Chiou, Brian; Davimes, Joshua; Gomez, Gimena; Grassi, Sara; Hoque, Ashfaqul; Karikari, Thomas K.; Kiffer, Frederico; Lopez, Mary; et al.
Abstract: Perception of our environment entirely depends on the close interaction between the central and peripheral nervous system. In order to communicate each other, both systems must develop in parallel and in coordination. During development, axonal projections from the CNS as well as the PNS must extend over large distances to reach their appropriate target cells. To do so, they read and follow a series of axon guidance molecules. Interestingly, while these molecules play critical roles in guiding developing axons, they have also been shown to be critical in other major neurodevelopmental processes, such as the migration of cortical progenitors. Currently, a major hurdle for brain repair after injury or neurodegeneration is the absence of axonal regeneration in the mammalian CNS. By contrasts, PNS axons can regenerate. Many hypotheses have been put forward to explain this paradox but recent studies suggest that hacking neurodevelopmental mechanisms may be the key to promote CNS regeneration. Here we provide a seminar report written by trainees attending the second Flagship school held in Alpbach, Austria in September 2018 organized by the International Society for Neurochemistry (ISN) together with the Journal of Neurochemistry (JCN). This advanced school has brought together leaders in the fields of neurodevelopment and regeneration in order to discuss major keystones and future challenges in these respective fields. Abstract : The Molecular mechanisms required for the proper wiring of both the Central Nervous System (CNS) as well as the Peripheral Nervous System (PNS) share similar features. However, once the CNS or PNS undergo a lesion or begin degenerating, both systems respond in distinctive ways. Here, we discuss recent advances and current challenges in the fields of neural development as well as regeneration.